Photoplethysmography in postoperative monitoring of deep inferior epigastric perforator (DIEP) free flaps. (28th December 2020) - Kyriacou, P A; Zaman, T; Pal, S K
Abstract: Objective : Deep inferior epigastric perforator (DIEP) free flaps are widely used as a reconstruction option following mastectomy in breast cancer. During such cases partial tissue necrosis can occur due to the insufficient blood supply to the transplanted tissue site. Therefore, monitoring of flap perfusion and early detection of flap failure is a prerequisite to flap survival. There is a need to develop a non-invasive, easy to use, reproducible and inexpensive monitoring device to assess flap perfusion postoperatively. Approach : A three-wavelength reflective optical sensor and processing system based on the principle of photoplethysmography (PPG) has been developed to investigate blood volumetric changes and estimate free flap blood oxygen saturation continuously and non-invasively in DIEP free flaps in the postoperative period. The system was evaluated in 15 patients undergoing breast reconstructive surgery using DIEP free flap. Main results and Significance : Good quality red, infrared and green PPG signals were obtained in the postoperative period. Initial estimation of blood oxygen saturation values estimated from the free flap PPGs seem to be in broad agreement with the commercial finger pulse oximeter used in this study. This pilot study has demonstrated that PPG has the potential to be used as a monitoring technique in assessing free flap viability.